Pengaruh Pertumbuhan Penjualan, Profitabilitas, Struktur Aktiva, Ukuran, Dan Likuiditas Terhadap Struktur Modal - Alfon, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study discusses to analyze and analyze the effect of growth, profitability, asset structure, firm size, and liquidity on capital structure in manufacturing companies listed on the Indonesia Stock Exchange for the period of 2015-2017. The purposive method used in determining samples with several criteria was obtained by 65 samples of manufacturing companies and using linear multiple regression analysis. The results showed that growth, profitability, asset structure, and firm size had no significant effect on capital structure while liquidity had a positive and significant effect on capital structure.